HR Development Strategy in Business Competition in The Digital Age - Alwy, Adenuddin; Sari Baso, Rachmie (International Journal of Social Science, Education, Communication and Economics, 2022)
This study aims to find the right strategy in optimizing human resources (HR) in industry in Indonesia, as one of the important aspects in facing business competition in the era of the industrial revolution 4.0. Using a literature study research method with data collection techniques used are questionnaires (questionnaires) and document studies. The data analysis technique used is through several stages, including collecting data, selecting data, displaying data, and drawing conclusions. Several strategies to optimize the development of Human Resources (HR) in Indonesia are, 1) Improving the quality and quantity of educational and training institutions 2) increasing the capacity and capability of the workforce.